A contribution to the study of copper production in the Iron Age polity of Paphos in Cyprus - Kassianidou, Vasiliki; Iacovou, Maria; Charalambous, Andreas; Ioannides, Demetrios; Degryse, Patrick; Agapiou, Athos; Zomeni, Zomenia; Ntinou, Maria; Georgiou, Artemis (My University, 2023)
This paper presents the results of the chemical, microscopic and isotopic analysis of an archaeometallurgical assemblage consisting of slag and metal samples from two Cypro-Classical monuments recently located within the urban landscape of the polity of Paphos, and from two slag heaps in the metalliferous region of the Paphos hinterland. The project identified technological changes and innovations, such as the introduction of new types of fluxes and the optimization of the smelting technology. Furthermore, the analysis of slag samples from one of the two monuments, identified as workshop complex on the plateau of the Paphian citadel, revealed the presence of an iron smithy. This pioneering interdisciplinary study paves the way for the development of a comparative archaeo-metallurgical project that will define the fingerprint of the Paphos copper deposits. The study was carried out in the context of the University of Cyprus-Leventis Foundation Project, “From the metalliferous sources to the citadel complex of ancient Paphos: Archaeo-environmental analysis of the mining and the built environment” (acronym MEANING 2017–2019).
Keywords: Copper smelting; Cyprus; Iron Age; Iron smithy; Late Antiquity; Lead Isotope Analysis; Paphos; Slag heap